Policing and politicising organised crime - Mann, Monique (Routledge studies in crime, security and justice, 2020)
Contexts, constructs and contestations -- The origins of organised crime -- Metaphors, monsters and moral entrepreneurs -- The politics of organised crime -- Organised crime and global (in)security -- Infrastructures, empires and enterprises -- The architecture of organised crime law -- The organised crime policing and intelligence enterprise -- Organised crime and onwards -- Epilogue: reflections and further considerations.